Transformation by appropriation of the free planned spaces in the Neighborhood Unit No 3 - Campos-García Calderón, Inés Magdalena (2022)
The Neighborhood Unit No 3 (UV3) was an approach to social housing based on the theory of the Neighborhood-Unit and the Satellite City, where Planned Open Spaces (POS) were relevant for the health and community development of the population. These were occupied and their physical-architectural characteristics were transformed. The objective of this research was to identify the transformation by appropriation of POS in UV3. Using a qualitative approach, a graphical comparative analysis of the original approach versus the current situation, documentary analysis and field observation were carried out. Changes were found identified based on the placement of material elements to delimit and subdivide spaces, and the incorporation of these to the residential space, changes in the use from collective green area to the individual space of the adjoining house, and the placement of symbolic elements of recognition. All of which result in different types of appropriation: according to the agent, the nature, and the consequences. It is concluded that the transformation of the POS from the original approach has been possible due to the disproportionate size of their areas, and is the result of different forms of appropriation that have generated an informal urban profile.